2018
DOI: 10.1038/s41393-018-0149-0
|View full text |Cite
|
Sign up to set email alerts
|

Does trans-spinal direct current stimulation modulate the Hoffmann reflexes of healthy individuals? A systematic review and meta-analysisc

Abstract: tsDCS did not affect the Hoffmann reflex, as shown in six studies. However, these findings come from studies with selection, performance and detection bias, and further research is needed to examine the effect of this intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…tsDCS, a promising noninvasive stimulation of central nervous system through a direct current over the spinal cord, emerged as an innovative tool [202]. In healthy individuals, although still debatable [203], tsDCS have been suggested to modulate spinal networks [204, 205]. Therefore, it is expected that tsDCS, modulates spinal function, and motor outcomes in subjects with SCI.…”
Section: Tdcs As a Motor Neurorehabilitation Tool In Neurological Dismentioning
confidence: 99%
“…tsDCS, a promising noninvasive stimulation of central nervous system through a direct current over the spinal cord, emerged as an innovative tool [202]. In healthy individuals, although still debatable [203], tsDCS have been suggested to modulate spinal networks [204, 205]. Therefore, it is expected that tsDCS, modulates spinal function, and motor outcomes in subjects with SCI.…”
Section: Tdcs As a Motor Neurorehabilitation Tool In Neurological Dismentioning
confidence: 99%
“…tDCS over the motor cortex has shown variable electrophysiological and behavioural effects and there is still no general consensus about its usefulness as a therapeutic technique for rehabilitation (Buch et al, 2017;Huang et al, 2017;Rothwell, 2016;Terranova et al, 2018). From the relatively few published studies on tsDCS in human participants a similar lack of consistency appears to be present at least in the case of electrophysiological measures such as MEPs and H-reflexes (Albuquerque et al, 2018;Bocci, Barloscio, et al, 2015;Bocci, Caleo, et al, 2015;Bocci, Marceglia, et al, 2015). In the present study, clear increases in MEP and in ballistic plantar flexion were observed in some participants, whereas in others, only modest or no effects were observed.…”
Section: Variability Of Effectsmentioning
confidence: 99%
“…Despite this, motor evoked potentials (MEPs) elicited by transcranial magnetic stimulation (TMS) of the primary motor cortex have been shown consistently to be facilitated by cathodal tsDCS and diminished by anodal tsDCS over the spinal segments where the motor neurons of the investigated muscle are located (Bocci, Barloscio, et al, 2015;Bocci, Marceglia, et al, 2015;Knikou, Dixon, Santora, & Ibrahim, 2015). Significantly, in the majority of studies a failure to demonstrate any changes in H-reflexes, which, at least in part, probes the excitability of the spinal motor neurons has been reported (Albuquerque, Mendonca, Campelo, Shirahige, & Monte-Silva, 2018). This suggests somewhat surprisingly that the functional effect of tsDCS is not necessarily related to effects on spinal motor neurons and interneurons locally, but may rather be related to a facilitation of corticospinal drive through increased excitability of corticospinal neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Mainly, the soleus H-reflex becomes excited by cathodal tsDCS and depressed by anodal tsDCS, resulting in homosynaptic depression. Moreover, presynaptic resistance and postactivation depression can be stimulated by tsDCS and can decrease spasticity by modulating interneuronal sensitivity [ 73 , 74 , 82 , 83 ]. In another study, Niérat et al [ 63 ] found that the cathodal part of tsDCS increases the respiratory neuromechanical element resulting in an increased tidal volume.…”
Section: Trans-spinal Direct Current Stimulation (Tsdcs)mentioning
confidence: 99%